Governance of Low-carbon Innovation in Domestic Energy Retrofits in the UK - Killip, G; Owen, A; Topouzi, M; Morgan, M (OpenExp, 2017)
Pioneering case studies of housing renovation show that 80-90% emissions reductions are achievable using existing technology, but the task requires very high standards of design, installation and integration of energy system components. The often-observed design-performance gap is related to how the industry is structured and construction projects are managed, not because of a fundamental lack of products and technologies. Many disciplinary studies have investigated aspects of the problem: technical potential, management practice, estimates for ‘green’ jobs, policy appraisal. However, little work has been done to understand the construction sector as potential agents of change in delivering and maintaining a low-energy housing stock. An inter-disciplinary approach is needed to understand the practices and processes of the institutions and firms in the market for repair, maintenance and improvement (RMI) of housing. RMI firms are incumbents in the housing-energy system in the sense that they are uniquely placed to reach and influence retrofit projects at scale. They make physical changes to buildings and also have influence on decisions through their everyday dealings with people. Four key questions are proposed to better understand the industry, the policy context, and the real nature of the low-carbon challenge for existing housing. How can the risks of doing retrofit badly (under-performance and unintended consequences) be better managed? What is the real economic opportunity of mass-scale housing retrofit? How well are supply chain actors and the vocational training system equipped to support the low-carbon challenge? Are the institutions of government and industry well aligned to support this transition?